The Effects of Implementing Green Roof Scenario on NO2 and Urban Hear Island Distribution in Yogyakarta City - Sukanti, Wahyuni; Sunarharum, Tri Mulyani (ASTONJADRO, 2024)
The development of urban areas requires a city to meet residential space needs which can have an impact on reducing green open space and causing derivative impacts in the form of decreasing air quality. The problem faced by the City of Yogyakarta in developing green open space is limited land, therefore innovation in green open space development is needed, one of which is developing green infrastructure by implementing a green roof scenario. So this research aims to analyze the application of the green roof scenario to air quality, especially in the distribution of Urban Heat Island (UHI) and Nitrogen Dioxide (NO2) in Yogyakarta City. The method used in this research are Landsat 8 images in 2021 with field observations and delineation of the potential area for green roofs at hotels and malls that have rooftops and the potential to implement green roofs. The research results show that implementing the green roof scenario in Yogyakarta can affect air quality. There are changes in the area that decrease the area in UHI class 4 (>3) from 4.74 Ha to 3.78 Ha and an increase in the Non-UHI area from 1,449.68 Ha to 1,731.57 Ha. Based on the NO2 parameter there has also been a change that increases in the area on a very good air quality scale from 406.80 Ha to 560.96 Ha, and a decrease in the area on a very poor scale from 23.71 Ha to 16.24 Ha. The results of the delineation of the UHI map, NO2 distribution, and spatial plans for Yogyakarta City show that locations with high UHI levels and poor NO2 quality are most widely distributed in Kemantren Gondokusuman, Umbulharjo, and Kotagede.